The Fight Against Child Trafficking Breaking the Cycle of Structural Violence (Taylor & Francis, 2023)
child trafficking; human trafficking; trafficking; anti-trafficking policies; EU-ASEAN; ASEAN; Human Rights; governance
English
Keywords: Family law: children; Human rights; International law; Politics & government; child trafficking; human trafficking; trafficking; anti-trafficking policies; EU-ASEAN; ASEAN; Human Rights; governance